2008
DOI: 10.1101/gad.1677208
|View full text |Cite
|
Sign up to set email alerts
|

Tpr directly binds to Mad1 and Mad2 and is important for the Mad1–Mad2-mediated mitotic spindle checkpoint

Abstract: The mitotic arrest-deficient protein Mad1 forms a complex with Mad2, which is required for imposing mitotic arrest on cells in which the spindle assembly is perturbed. By mass spectrometry of affinity-purified Mad2-associated factors, we identified the translocated promoter region ( Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
156
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(174 citation statements)
references
References 24 publications
15
156
1
Order By: Relevance
“…Cells were then permeabilized with 0.2% Triton-X 100 in PBS (PBS-T) for 3 min, and were blocked in 3% BSA in PBS-T for 30 min, followed by incubation with appropriate antibodies. 38,39 To detect kinetochore MTBP, H-40 antibody (Santa Cruz Biotechnology) was used. Z-sectioned images were obtained on a Zeiss Axioplan II deconvolution microscope (Carl Zeiss, Thornwood, NY, USA) and processed as described by Guenther et al 40 Flow cytometric analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then permeabilized with 0.2% Triton-X 100 in PBS (PBS-T) for 3 min, and were blocked in 3% BSA in PBS-T for 30 min, followed by incubation with appropriate antibodies. 38,39 To detect kinetochore MTBP, H-40 antibody (Santa Cruz Biotechnology) was used. Z-sectioned images were obtained on a Zeiss Axioplan II deconvolution microscope (Carl Zeiss, Thornwood, NY, USA) and processed as described by Guenther et al 40 Flow cytometric analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Tpr phosphorylated at S2059 associates with chromatin during telophase Tpr and its orthologs have been shown to be crucial for the progression of mitosis across different species (Lee et al, 2008;Lince-Faria et al, 2009;Nakano et al, 2010;Niepel et al, 2005). Immunofluorescence analysis using antibodies against Tpr and Tpr-pS2059 showed that the distribution of S2059-phosphorylated Tpr was the same as that of the Tpr protein during interphase and all the way up to metaphase (Fig.…”
Section: Tpr Is Phosphorylated At Residues S2059 and S2094 In Vivomentioning
confidence: 96%
“…Mad1 and Mad2 proteins have been shown to regulate the mitotic spindle checkpoint by inhibiting the Cdc20-APC complex (Dobles et al, 2000;Fang et al, 1998;Li and Benezra, 1996;Li et al, 1997). Tpr has been shown to directly interact with Mad1 and Mad2 proteins through its amino-and carboxy-terminal regions, respectively (Lee et al, 2008). We have previously shown that phosphorylation of Tpr by ERK2 enhances its interaction with ERK2 (Vomastek et al, 2008).…”
Section: Tpr Is Phosphorylated At Residues S2059 and S2094 In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, a widely conserved protein, Megator, has been recently implicated in anaphase chromosome movement [190], through a specific role in spindle elongation. Surprisingly, this protein and its human counterpart Tpr, were shown to be required for an efficient SAC response, and its depletion accelerated anaphase entry [190,191].…”
Section: The Spindle Matrixmentioning
confidence: 99%